2021
DOI: 10.1364/josab.419348
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of a ring Airy vortex beam in slant atmospheric turbulence

Abstract: In this paper, the propagation characteristics of a ring Airy vortex beam (RAVB) in slant atmospheric turbulence are studied. The effects of some key parameters, such as the truncation factor, the zenith angle, and the propagation distance, on the propagation characteristics of RAVB are analyzed. The results show that the beam quality becomes worse with an increase in the propagation distance, zenith angle, and truncation factor. When the propagation distance exceeds 3 km in turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…14(a)) [178]. Such FSO links have been studied using different types of beams such as nonuniformly correlated Bessel beams (NUCBs) [179], Airy beams [180][181][182][183][184], OAM beams [185][186][187][188], and complex multi-vortex beams [189]. Since BG beams change from a Bessel structure to an annular ring, this is a disadvantage for long-range communication.…”
Section: Optical Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…14(a)) [178]. Such FSO links have been studied using different types of beams such as nonuniformly correlated Bessel beams (NUCBs) [179], Airy beams [180][181][182][183][184], OAM beams [185][186][187][188], and complex multi-vortex beams [189]. Since BG beams change from a Bessel structure to an annular ring, this is a disadvantage for long-range communication.…”
Section: Optical Communicationmentioning
confidence: 99%
“…With a two Bessel beam multiplexed system, where each beam carried data of 10 Gbaud (40 Gbit s −1 ) 16-ary quadrature amplitude modulation (16-QAM), effective suppression of the inter-channel crosstalk, as well as an improvement in the bit-rate performance and recuperating the nondiffracting property were all experimentally demonstrated (figure 14(a)) [181]. Such FSO links have been studied using different types of beams such as nonuniformly correlated Bessel beams [185], Airy beams [186][187][188][189][190], OAM beams [191][192][193][194], and complex multi-vortex beams [195,196,197]. Since BG beams change from a Bessel structure to an annular ring, this is a disadvantage for long-range communication.…”
Section: Optical Communicationmentioning
confidence: 99%
“…In the past decades, numerous efforts have been devoted to the propagation of partially coherent (PC) beams in atmospheric turbulence due to their important applications in freespace optical communications, lidar distance measurement and remote sensing [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It is generally considered that atmospheric turbulence causes a series of harmful turbulence effects such as scintillation (i.e., intensity fluctuation), phase distortion and so on, which will lead to an increase in the communication error rate and decrease in the channel capacity of the system [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of practical importance to develop a method to overcome or reduce turbulence effects. It is demonstrated that one may use special beams to achieve this goal [6][7][8][9][10][11][12][13][14][15]. A PC beam is more suitable for propagation in turbulent media than a fully coherent beam because it is less affected by turbulent media and can effectively mitigate harmful optical phenomena such as beam spreading, drift, scintillation, speckles and uneven intensity distribution [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation